Interpersonal communications in nursing practice - Key to Quality Health care - Brinderjeet Kaur (Archives of Nursing Practice and Care - Peertechz Publications, 2020)
Interpersonal communication is one of the foundations of quality patient care especially for valuable trio in health care- the doctor, the nursing staff and the patient. Effective communication skills in health care setting are a boon as they not only benefit patient but also the health care provider, in respect to job satisfaction and prevention of work stress which affect health. There is strong need of hour that more training, more awareness is created about barriers to effective communication and empower them with strategies to enhance their receptivity towards patient's queries thereby improving nursing interventions in patient care.